The impact of energy consumption on Carbon Intensity of Human Well-Being (CIWB) - Nguyen Thuan; Dang Bac Hai (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration, 2021)
A key concern when constructing sustainable development policy is reducing the negative impact on environmental systems and maximizing human welfare. In this study, we assess how energy consumption effected on Carbon intensity of human well-being (CIWB). Using two-way fixed effects in panel regression, this relationship has been investigated during 2000-2018 for 9 lower middle-income countries including Algeria, Bangladesh, Egypt, India, Morocco, Pakistan, Philippines, Uzbekistan and Vietnam, while adding GDP and FDI per capita as control variables. The study reveals that the use of energy for economic development is ineffective and inconsistent with the overview of sustainable development due to the result of increasing CIWB. However, the sign of negative coefficients of GDP and FDI per capita in control variables have given the striking findings that these factors will be helpful for lower middle - income countries to pursue sustainable development by reducing CIWB.